5-(Phenylthio)-3H-pyrrole-4-carbonitriles as effective corrosion inhibitors for mild steel in 1 M HCl: Experimental and theoretical investigation - Verma C.B.; Ebenso E.E.; Bahadur I.; Obot I.B.; Quraishi M.A. (My University, 2025)
The adsorption and inhibition effects of three 5-(phenylthio)-3H-pyrrole-4-carbonitriles (PPCs) namely: 2-amino-3-methyl-3-phenyl-5-(phenylthio)-3H-pyrrole-4-carbonitrile (PPC I), 2-amino-3-(4-hydroxyphenyl)-3-methyl-5-(phenylthio)-3H-pyrrole-4-carbonitrile (PPC II), and 2-amino-3-(2,4-dihydroxyphenyl)-3-methyl-5-(phenylthio)-3H-pyrrole-4-carbonitrile (PPC III) on mild steel corrosion in 1 M HCl have been studied by experimental and theoretical methods. Results showed that inhibition efficiency increases with concentration and maximum value was obtained at 50 mg/L concentration. From the results it is concluded that the PPCs inhibited mild steel corrosion in 1 M HCl by adsorbing on the metal surface. Polarization results showed that the PPCs act as anodic type inhibitors. The surface morphology study was carried out by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The Monte Carlo simulation were found to be in good agreement with the experimental results. © 2015 Published by Elsevier B.V. All rights reserved.